Factors governing the performance of Auxiliary Nurse Midwives in India: A study in Pune district. - Thidar Pyone; Shilpa Karvande; Somasundari Gopalakrishnan; Vidula Purohit; Sarah Nelson; Subha Sri Balakrishnan; Nerges Mistry; Matthews Mathai (PLoS ONE)
Background The Auxiliary nurse midwife (ANM) cadre was created to focus on maternal and child health. ANMs are respected members of their communities and established providers of maternal and child health care within the community and at the facility level. Over time, additional roles and responsibilities have been added. Despite the importance of ANMs in the primary healthcare system in India, studies that consider factors governing the performance of ANMs in their workplaces are limited. We aimed to study factors governing performance of ANMs in Pune district, India. Methods Semi-structured interviews were conducted with 13 purposely selected key informants at facility, district, state, and national levels. Focus group discussions were conducted with 41 ANMs and 25 members of the community. Non-participatory observations with eight ANMs provided information to expand on and scrutinise findings that emerged from the other lines of inquiry. A realist lens was applied to identify ANMs' performance as a result of "mechanisms" (training, supervision, accountability mechanisms) within the given "context" (regulatory system, infrastructure and resources, ANMs' expanded scope of work, gender roles and norms). Results Weak enforcement of regulatory system led to poor standardisation of training quality among training institutions. Challenges in internal accountability mechanisms governing ANMs within the health system hierarchy made it difficult to ensure individual accountability. Training and supervision received were inadequate to address current responsibilities. The supervisory approach focused on comparing information in periodic reports against expected outputs. Clinical support in workplaces was insufficient, with very little problem identification and solving. Conclusion Focusing on the tasks of ANMs with technical inputs alone is insufficient to achieve the full potential of ANMs in a changing context. Systematic efforts tackling factors governing ANMs in their workplaces can produce a useful cadre, that can play an important role in achieving universal health coverage in India.